Introduction to Oracle9i SQL and PL/SQL (1Z0-007) : Oracle certification. - Powell, Gavin; Safari eBooks ([S.l.] : VTC, 2003)
"Virtual Training Company's Introduction to Oracle SQL and PL/SQL tutorial will cover the relational Database Model, the Oracle Architecture and the Physical database. The tutorial is aimed at programmers, and individuals who have had prior SQL and relational database experience. Gavin Powell, your instructor, will begin teaching you many Oracle tools such as the SQL Plus, SQL Plus Worksheet, and Oracle Enterprise Manager. This tutorial will explain how to maintain the Logical Database, and the difference between the Logical Database and the Physical database. You will be guided, in great detail, in the following areas: retrieving, changing, adding, and deleting data from the Database. From there, you will learn about Logical Database objects, Security, Select Statements, and much more. Introduction to Oracle SQL and PL/SQL will cover areas for the Oracle Certification course (1Z0-007)"--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher.
Date of publication from resource description page (viewed Feb. 23, 2010).
Instructor: Gavin Powell.
Keywords: SQL (Computer program language); PL/SQL (Computer program language); Oracle (Computer file); Electronic books